Individual Poverty Measurement Using a Fuzzy Intrahousehold Approach - Gianni Betti; Lucia Mangiavacchi; Luca Piccoli (Institute of Labor Economics (IZA), 2017)
This work studies the impact of accounting for intrahousehold inequality in the distribution of resources for the measurement of poverty. For the estimation of intrahousehold distribution of resources the study relies on collective Engel curves. For the poverty analysis, we propose a fuzzy intrahousehold index which is less sensitive to small changes around the poverty line compared to standard FGT indices and produce more reliable results. This provides an interesting approach to address individual poverty in contexts where intrahousehold inequality is at work and there is a concentration of individuals near the poverty line. The proposed approach is applied to the analysis of individual poverty in Albania, finding an expected general increase in poverty rates. Besides, a previously unperceived issue – female poverty – emerges as a worryingly aspect to be accounted for in anti-poverty policies.
Keywords: I32; J16; D13; 330; female poverty; gender inequality; fuzzy set poverty; intrahousehold distribution; collective model; Albania